In silico analysis of binding sites for potential inhibitors targeting the complex of furin protease - Khmil, N. V.; Shestopalova, A. V.; Kolesnikov, V. G. (Biophysical Bulletin, 2025)
Background. COVID-19 is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Efforts to fight the virus include the development and investigation of vaccines, monoclonal antibodies, and specific antiviral drugs targeting key stages in the viral life cycle. Objectives. The aim of the study is to investigate the binding sites of furin protease with the SARS-CoV-2 spike protein (S protein) in different conformations and to evaluate the binding affinities of non-specific antiviral drugs and the macrocyclic peptidomimetic inhibitor 8 (PI8) to the S protein–furin protease complexes using a molecular docking approach. Material and Methods. The three-dimensional structures of the S protein (PDB IDs: 6VYB, 6VXX, 7VHJ) from the Protein Data Bank (www.rcsb.org ) were docked with furin protease (PDB ID: 5JXG) using the ClusPro 2.0 server. Non-specific antiviral drugs, such as remdesivir, chloroquine, favipiravir, nelfinavir, and PI8, were docked onto 6VYB-5JXG, 6VXX-5JXG, and 7VHJ-5JXG complexes using the AutoDock Vina program. The ligands were energy-minimized using the Universal Force Field (UFF) and converted to PDBQT format with OpenBabel. Protein optimization was performed using AutoDock Tools. Docking results were visualized using the Discovery Studio 2024 Visualizer. Results. The binding affinity of the studied ligands with the S protein-furin protease complexes was verified by molecular docking studies. PI8, nelfinavir, and remdesivir showed high binding affinity with the 7VHJ-5JXG structure due to the presence of amino acid residues at the furin cleavage site. The best docking scores of PI8 with 6VYB-5JXG, 6VXX-5JXG, and 7VHJ-5JXG complexes were -9.7 kcal/mol, -9.5 kcal/mol, and -9.9 kcal/mol, respectively. The interaction between the S protein-furin complexes and PI8 involves specific amino acid residues, primarily within the catalytic site of furin and the reactive site loop of PI8. Docking studies showed that remdesivir acts directly on the furin cleavage site of the S protein (in the 7VHJ-5JXG complex), forming energetically favorable interactions through hydrogen bonds and hydrophobic contacts, with a high binding affinity (binding energy score is -9.1 kcal/mol). The energetically favorable interactions of the 6VYB-5JXG, 6VXX-5JXG, and 7VHJ-5JXG complexes with nelfinavir are also confirmed by their low binding energy scores of -8.2 kcal/mol, -8.9 kcal/mol, and -9.3 kcal/mol, respectively. Conclusion. According to the results of molecular docking, PI8, nelfinavir, and remdesivir demonstrate energetically favorable interactions with the studied complexes and can be considered promising inhibitors targeting the SARS-CoV-2 S protein–furin protease complexes.